Fecal calprotectin is a clinically relevant biomarker of mucosal healing in patients with quiescent ulcerative colitis. Issue 1 (January 2016) - Yamaguchi, Sayaka; Takeuchi, Yoshiaki; Arai, Katsuhito; Fukuda, Katsuyuki; Kuroki, Yuichiro; Asonuma, Kunio; Takahashi, Hiroshi; Saruta, Masayuki; Yoshida, Hitoshi
Abstract: Background and Aim: Calprotectin is an abundant protein in neutrophils, which infiltrate the mucosa during inflammation. Fecal calprotectin (FC) level has shown correlation with disease activity in ulcerative colitis (UC) patients. Additionally, FC level is expected to indicate mucosal healing (MH). This study was to see the significance of FC for predicting MH in patients with quiescent UC. Methods: A total of 112 patients with quiescent UC were included. After taking blood and stool samples, patients underwent total colonoscopy, and the Mayo endoscopic subscore was recorded. FC was measured by fluorescence enzyme immunoassay. C‐reactive protein, hemoglobin, erythrocyte sedimentation rate, and serum albumin were measured as conventional biomarkers. MH was defined as Mayo 0 or 0 and 1, and receiver–operator characteristic analyses were undertaken to determine the significance levels of measurements. Results: Data from 105 patients were available. Eleven patients showed Mayo ≥ 2. The median (interquartile range) of FC level of all patients was 115 µg/g (45.4–420). The area under the curve (AUC) in receiver operator characteristic analysis of FC to predict Mayo 0 and 1 was 0.869 with a cut‐off value of 200 µg/g yielding 67% sensitivity and 91% specificity, which were the best among all biomarkers. However, the power of FC to predict Mayo 0 was modest; the AUC was 0.639 and cut‐off value 194 µg/g with 71% sensitivity and 58% specificity. Conclusions: Based on the findings of this study, we believe that FC is a clinically relevant biomarker of MH in patients with quiescent UC. Other favorable features of FC test include feasibility and non‐invasiveness.